Perkawinan Lansia di Kecamatan Socah Kabupaten Bangkalan Perspektif Maqasid Al-Shari’ah - Roisul Umam Hamzah (State Islamic University (UIN) of Sunan Ampel, 2018)
This is a field research that analyzes the marriage suitability of elderly people in Socah, Bangkalan under the theory of maqasid shari'ah. The elderly marriage is officially conducted at KUA (Religious Affairs Office) of Socah for different reasons, namely: on the basis of coercion to the bride so that the family relationship does not break up, resulting in reluctance, on the basis of family compassion and encouragement. It is because the bride is an old maid and is his own niece on the basis of mutual love, avoid immorality and seek peace of life in old age. All couples can fulfill both material and non-material obligations, although not as perfect as a young couple. Some husbands do not want to have children for fear of not being able to support even though in this case the wife really wants it. Thus, the marriage of the elderly in Socah is sometimes appropriate and not in accordance with the maqasid shari'ah. The suitability in question is in terms of hifz al-din (protecting religion) and hifz al-mal (protecting wealth), while its inadequacies are in terms of hifz al-nasl (protecting offspring), because of their desires to have offspring and in terms of hifz al-nafs (protecting soul), and hifz al-'aql (protecting ratio), because of differences in descent have the negative effect on family disharmony that can interfere with the soul and mind. In this case, an intense dialogue and approach must be made to the couple to be more open and understand each other.